Diseño básico de una conexión de un parque eólico Offshore implementando tecnología HVDC-VSC (2017)
"The main objective of this project is to make the basic design of a 600MW offshore wind farm connection through an HVDC line of 400 km using VSC technology to the Kundur system of 230 kV. In order to achieve this objective, it was necessary to model the wind farm to determine the different generation conditions, determine the voltage level and the optimum caliber for the DC transmission line, and accomplish the basic design of the inverter and rectifier substations (specification of transformers, DC filters, damping reactors and line conductor). Additionally, a reliability analysis was performed using Markov chains to select the type of transmission line configuration along with the different reliability indexes (LOEE, LOLP, DNS, EIR, etc.) and an approximate cost of the project was determined (without considering the cost of the wind farm), taking into account the useful life and the losses of the line, which was compared with the cost of similar projects".-- Tomado del Formato de Documento de Grado.